A Qualitative Study of Factors Influencing Food Choices and Food Sources Among Adults Aged 50 Years and Older During the Coronavirus Disease 2019 Pandemic - Patrick J. Brady; Natoshia M. Askelson; Helaina Thompson; Sarah Kersten; Haley Hopkins; Sato Ashida; Faryle Nothwehr; Brandi Janssen; David Frisvold (Journal of the Academy of Nutrition and Dietetics, 2023)

Why human rights matter for marine conservation - Patrick Smallhorn-West; Edward Allison; Georgina Gurney; Divya Karnad; Heidi Kretser; Aaron Savio Lobo; Sangeeta Mangubhai; Helen Newing; Kamille Pennell; Sushil Raj; Alexander Tilley; Haley Williams; et al. (Frontiers in Marine Science, 2023)
Human rights matter for marine conservation because people and nature are inextricably linked. A thriving planet cannot be one that contains widespread human suffering or stifles human potential; and a thriving humanity cannot exist on a dying planet. While the field of marine conservation is increasingly considering human well-being, it retains a legacy in some places of protectionism, colonialism, and fortress conservation. Here, we i) provide an overview of human rights principles and how they relate to marine conservation, ii) document cases where tensions have occurred between marine conservation goals and human rights, iii) review the legal and ethical obligations, and practical benefits, for marine conservation to support human rights, and iv) provide practical guidance on integrating human rights principles into marine conservation. We argue that adopting a human rights-based approach to marine conservation, that is integrating equity as a rights-based condition rather than a charitable principle, will not only help meet legal and ethical obligations to respect, protect, and fulfil human rights, but will also result in greater and more enduring conservation impact.

Lagrangian surface signatures reveal upper-ocean vertical displacement conduits near oceanic density fronts - H.M. Aravind; Vicky Verma; Sutanu Sarkar; Mara A. Freilich; Amala Mahadevan; Patrick J. Haley; Pierre F.J. Lermusiaux; Michael R. Allshouse (Ocean Modelling, 2023)

Virulence evolution during a naturally occurring parasite outbreak - Camden D. Gowler; Haley Essington; Bruce O’Brien; Clara L. Shaw; Rebecca W. Bilich; Patrick A. Clay; Meghan A. Duffy (Evolutionary Ecology, 2023)
Virulence, the degree to which a pathogen harms its host, is an important but poorly understood aspect of host-pathogen interactions. Virulence is not static, instead depending on ecological context and potentially evolving rapidly. For instance, at the start of an epidemic, when susceptible hosts are plentiful, pathogens may evolve increased virulence if this maximizes their intrinsic growth rate. However, if host density declines during an epidemic, theory predicts evolution of reduced virulence. Although well-studied theoretically, there is still little empirical evidence for virulence evolution in epidemics, especially in natural settings with native host and pathogen species. Here, we used a combination of field observations and lab assays in the Daphnia - Pasteuria model system to look for evidence of virulence evolution in nature. We monitored a large, naturally occurring outbreak of Pasteuria ramosa in Daphnia dentifera , where infection prevalence peaked at ~ 40% of the population infected and host density declined precipitously during the outbreak. In controlled infections in the lab, lifespan and reproduction of infected hosts was lower than that of unexposed control hosts and of hosts that were exposed but not infected. We did not detect any significant changes in host resistance or parasite infectivity, nor did we find evidence for shifts in parasite virulence (quantified by host lifespan and number of clutches produced by hosts). However, over the epidemic, the parasite evolved to produce significantly fewer spores in infected hosts. While this finding was unexpected, it might reflect previously quantified tradeoffs: parasites in high mortality (e.g., high predation) environments shift from vegetative growth to spore production sooner in infections, reducing spore yield. Future studies that track evolution of parasite spore yield in more populations, and that link those changes with genetic changes and with predation rates, will yield better insight into the drivers of parasite evolution in the wild.

Energy and Momentum Lost to Wake Eddies and Lee Waves Generated by the North Equatorial Current and Tidal Flows at Peleliu, Palau - Shaun Johnston; Jennifer MacKinnon; Patrick Colin; Patrick Haley; Pierre Lermusiaux; Andrew Lucas; Mark Merrifield; Sophia Merrifield; Chris Mirabito; Jonathan Nash; Celia Ou; Mika Siegelman; et al. (Oceanography, 2019)

Heterogeneous distribution of trastuzumab in HER2-positive xenografts and metastases: role of the tumor microenvironment - Jennifer Hazel Elizabeth Baker; Alastair Hugh Kyle; Stefan Alexander Reinsberg; Firas Moosvi; Haley Margaret Patrick; Jordan Cran; Katayoun Saatchi; Urs Häfeli; Andrew Ivor Minchinton (Clinical & Experimental Metastasis, 2018)

Optimal Planning and Sampling Predictions for Autonomous and Lagrangian Platforms and Sensors in the Northern Arabian Sea - Pierre Lermusiaux; Patrick Haley; Sudip Jana; Abhinav Gupta; Chinmay Kulkarni; Chris Mirabito; Wael Ali; Deepak Subramani; Arkopal Dutt; Jing Lin; Andrey Shcherbina; Craig Lee; et al. (Oceanography, 2017)

Validation of quantitative trait loci for grain quality-related traits in a winter wheat mapping population - Hung Quoc Dao; Patrick F. Byrne; Scott D. Reid; Scott D. Haley (Euphytica, 2017)

Validation of genetic algorithm-based optimal sampling for ocean data assimilation - Kevin D. Heaney; Pierre F. J. Lermusiaux; Timothy F. Duda; Patrick J. Haley (Ocean Dynamics, 2016)

Root traits contributing to drought tolerance of synthetic hexaploid wheat in a greenhouse study - Steven R. Becker; Patrick F. Byrne; Scott D. Reid; William L. Bauerle; John K. McKay; Scott D. Haley (Euphytica, 2016)

Time-optimal path planning in dynamic flows using level set equations: realistic applications - Tapovan Lolla; Patrick J. Haley; Pierre F. J. Lermusiaux (Ocean Dynamics, 2014)

Time-optimal path planning in dynamic flows using level set equations: theory and schemes - Tapovan Lolla; Pierre F. J. Lermusiaux; Mattheus P. Ueckermann; Patrick J. Haley (Ocean Dynamics, 2014)

A relocatable ocean model in support of environmental emergencies - Michela De Dominicis; Silvia Falchetti; Francesco Trotta; Nadia Pinardi; Luca Giacomelli; Ernesto Napolitano; Leopoldo Fazioli; Roberto Sorgente; Patrick J. Haley; Pierre F. J. Lermusiaux; Flavio Martins; Michele Cocco (Ocean Dynamics, 2014)

Genome-wide association mapping of yield and yield components of spring wheat under contrasting moisture regimes - Erena A. Edae; Patrick F. Byrne; Scott D. Haley; Marta S. Lopes; Matthew P. Reynolds (Theoretical and Applied Genetics, 2014)

Circulation and Intrusions Northeast of Taiwan: Chasing and Predicting Uncertainty in the Cold Dome - Glen Gawarkiewicz; Sen Jan; Pierre Lermusiaux; Julie McClean; Luca Centurioni; Kevin Taylor; Bruce Cornuelle; Timothy Duda; Joe Wang; Yiing Jiang Yang; Thomas Stanford; Ren-Chieh Lien; et al. (Oceanography, 2011)

Multiscale Physical and Biological Dynamics in the Philippine Archipelago: Predictions and Processes - Pierre Lermusiaux; Patrick Haley; Wayne Leslie; Arpit Agarwal; Oleg Logutov; Lisa Burton (Oceanography, 2011)

Multiscale two-way embedding schemes for free-surface primitive equations in the “Multidisciplinary Simulation, Estimation and Assimilation System” - Patrick J. Haley; Pierre F. J. Lermusiaux (Ocean Dynamics, 2010)

Glutenin allelic variation and 1AL.1RS effects on dough mixing properties of wheat grown in irrigated and rainfed environments - Shusong Zheng; Patrick F. Byrne; Scott D. Haley; Xueyan Shan; Scott D. Reid (Euphytica, 2010)

Quantifying Uncertainties in Ocean Predictions - Pierre Lermusiaux; Ching-Shang Chiu; Glen Gawarkewicz; Phil Abbot; Allan Robinson; Robert Miller; Patrick Haley; Wayne Leslie; Sharanya Majumdar; Alex Pang; Francois Lekien (Oceanography, 2006)